2014
DOI: 10.1111/dsu.12463
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Botulinum Toxin A in Aesthetic Treatments: A Systematic Review of Clinical Studies

Abstract: The short-term safety profile of BoNT-A in cosmetic nonsurgical procedures was confirmed for all the three commercial formulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
68
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 52 publications
(179 reference statements)
4
68
0
8
Order By: Relevance
“…This excellent safety profile is in line with previous studies where BTA was injected in the glabella for aesthetic reasons [23,24]. The safety and tolerability of BTA is one that has been studied extensively; however future studies on BTA for depression should continue to monitor safety data, as this is the largest study to date to report on safety for this specific indication.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…This excellent safety profile is in line with previous studies where BTA was injected in the glabella for aesthetic reasons [23,24]. The safety and tolerability of BTA is one that has been studied extensively; however future studies on BTA for depression should continue to monitor safety data, as this is the largest study to date to report on safety for this specific indication.…”
supporting
confidence: 82%
“…BTA as a treatment for depression offers some favorable properties. It is unique as a "one-time dose" intervention with an effect that lasts for months, it has an excellent safety and tolerability record, and it is already approved as a treatment of glabellar frown lines [23,24,27]. Furthermore, when taking into account the cost of brand medications and psychotherapy, it can be a cost-effective intervention for certain patient populations [28].…”
mentioning
confidence: 99%
“…The chemoimmobilizing effect of BTA injections on facial muscles and its safe use for aesthetic correction of facial rhytids and mild soft tissue ptosis is very well established scientifically and clinically [17,18,19,20]. A group of researchers showed that botulinum toxin type A directly inhibited fibroblast-tomyofibroblast differentiation in a cell culture derived from hypertrophic scars, but they observed no such effect in a culture derived from normotrophic scars [1].…”
Section: General Considerationsmentioning
confidence: 99%
“…В отличие от сибиреязвенного токсина, который вызывает системные повреждения органов и тканей, действие ботулотокси-нов может быть полностью обратимо, и при адекватной терапии интоксикация не имеет каких-либо послед-ствий. Данное свойство, а также механизм действия предопределили использование ботулотоксина в меди-цине при многочисленных спастических и связанных с ними болевых синдромах, а также в косметологии [44,45]. Успешное и широкое медицинское и косметическое применение ботулотоксина служит одной из причин, по которым вакцинация против наиболее широко встреча-ющихся токсинов типа А и В не получила распростране-ния.…”
Section: ботулиническая токсикоинфекцияunclassified